2021
DOI: 10.3390/bioengineering8070086
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Clinical Study Investigating the Thermal Physiology of Breast Cancer via High-Resolution Infrared Imaging

Abstract: This descriptive study investigates breast thermal characteristics in females histologically diagnosed with unilateral breast cancer and in their contralateral normal breasts. The multi-institutional clinical pilot study was reviewed and approved by the Institutional Review Boards (IRBs) at participating institutions. Eleven female subjects with radiologic breast abnormalities were enrolled in the study between June 2019 and September 2019 after informed consent was obtained. Static infrared images were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In a study on breast cancer screening datasets, thermal patterns were applied to track vasodilation and blood formation, which showed verification of changes in thermal characteristics of the breast area for cancer leading abnormalities (CLA) [11,15,29]. The results were obtained using different matrix factorization techniques, i.e., NMF [16] and Deep semiNMF [9] and bases embedding [8,9] and were compared with those obtained from other low-rank matrix approximation algorithms to provide a comprehensive analysis [25].…”
Section: Resultsmentioning
confidence: 99%
“…In a study on breast cancer screening datasets, thermal patterns were applied to track vasodilation and blood formation, which showed verification of changes in thermal characteristics of the breast area for cancer leading abnormalities (CLA) [11,15,29]. The results were obtained using different matrix factorization techniques, i.e., NMF [16] and Deep semiNMF [9] and bases embedding [8,9] and were compared with those obtained from other low-rank matrix approximation algorithms to provide a comprehensive analysis [25].…”
Section: Resultsmentioning
confidence: 99%
“…Tumor thermography as an imaging technique based on tumor thermogenesis has been widely employed as a screening tool for BC due to the advantages of no-radiation, objective evaluation, and non-invasiveness ( Hakim and Awale, 2020 ; Lozano et al, 2020 ). In the past, tumor thermogenesis has been mainly attributed to several pro-tumor factors, including tumor metabolism, angiogenesis, and the pro-tumor immune microenvironment ( Shi et al, 2015 ; Gandhi et al, 2021 ; Lozano et al, 2021 ). Kawashima et al reported that UCP1 induced thermogenesis in BC cell lines ( Kawashima et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%